Astrogliosis Associated With Behavioral Abnormality in a Non-anaphylactic Mouse Model of Cow's Milk Allergy - Smith, Nicholas A.; Germundson, Danielle L.; Combs, Colin K.; Vendsel, Lane P.; Nagamoto-Combs, Kumi (Frontiers in Cellular Neuroscience, 2019)
Etiology of neuropsychiatric disorders is complex, involving multiple factors that can affect the type and severity of symptoms. Although precise causes are far from being identified, allergy or other forms of hypersensitivity to dietary ingredients have been implicated in triggering or worsening of behavioral and emotional symptoms, especially in patients suffering from depression, anxiety, attention-deficit hyperactivity, and/or autism. Among such ingredients, cow’s milk, along with wheat gluten, is commonly suspected. However, the contributory role of cow’s milk in these disorders has not been elucidated due to insufficient pathophysiological evidence. In the present study, we therefore investigated neuroinflammatory changes that are associated with behavioral abnormality using a non-anaphylactic mouse model of cow’s milk allergy. Male and female C57BL/6J mice were subjected to a 5-week oral sensitization procedure without or with a major milk allergen, beta-lactoglobulin (BLG). All mice were challenged with BLG and their anxiety- and depression-associated behaviors were subsequently assessed during the 6th and 7th weeks. We found that BLG-sensitized male mice exhibited significantly increased anxiety- and depression-like behavior although they did not display anaphylactic reactions when challenged with BLG. Female behavior was not noticeably affected by BLG sensitization. Upon examination of the small intestines, reduced immunoreactivity to occludin was detected in the ileal mucosa of BLG-sensitized mice although the transcriptional expression of this tight-junction protein was not significantly altered when measured by quantitative RT-PCR. On the other hand, the expression of tumor necrosis factor alpha (TNFα) in the ileal mucosa was significantly elevated in BLG-sensitized mice, suggesting the sensitization had resulted in intestinal inflammation. Inflammatory responses were also detected in the brain of BLG-sensitized mice, determined by the hypertrophic morphology of GFAP-immunoreactive astrocytes. These reactive astrocytes were particularly evident near the blood vessels in the midbrain region, resembling the perivascular barrier previously reported by others in experimental autoimmune encephalitis mouse models. Interestingly, increased levels of TNFα was also found in this region. Taken together, our results demonstrated that BLG sensitization elicits inflammatory responses in the intestine and brain without overt anaphylactic signs of milk allergy, signifying food allergy as a potential pathogenic factor of neuropsychiatric disorders.